A web interface for wireless mesh networks based on heuristic algorithms: optimisation and analysis for different scenarios. (2015) - Lala, Algenti; Kolici, Vladi; Oda, Tetsuya; Barolli, Leonard; Barolli, Admir; Xhafa, Fatos
In this work, we present WMN-HC and WMN-SA systems which are based on Hill Climbing (HC) and Simulated Annealing (SA) for location assignment of mesh routers in Wireless Mesh Networks (WMNs). As evaluation metrics, we used throughput, one-way delay, jitter, fairness index and residual energy. The simulation results show that for WMN-HC, the throughput of 24 mesh routers is good for both WMN architectures. But, for WMN-SA, the throughput is almost the same. For WMN-HC, the delay and jitter of 24 mesh routers is low for both WMN architectures. However, for WMN-SA, the delay and jitter of 32 mesh routers is higher for I/B WMN architecture. For WMN-HC, the fairness index of 16 mesh routers is high for Hybrid WMN architecture. But, for WMN-SA, the fairness index of 32 mesh routers is high for I/B WMN architecture. For 16 and 32 mesh routers, the remaining energy of WMN-HC is higher than WMN-SA.